The alveolar epithelial differentiation of glandular inner lining cells in a mucoepidermoid carcinoma of the lung: a case report - Xu Hong-Tao; Lin Xu-Yong; Li Qing-Chang; Wang En-Hua (BMC, 2012)
Abstract Mucoepidermoid carcinoma is a common malignant epithelial tumor of salivary glands, but relatively rare in lung. The histological features of mucoepidermoid carcinoma of the lung are similar to its counterpart arising from the salivary glands. Here, we reported a special tumor that occurred in the medial segment of the right lower lobe in a 22-year-old man. This tumor exhibited typical features of mucoepidermoid carcinoma with 3 cell types: squamoid cells, mucin-secreting cells and cells of intermediate type. These 3 types of cells organized into cysts, nests, glands and solid patterns. Specially, the inner lining cells of some glandular structures were uniform cuboidal and hobnail-like, similar to the alveolar epithelial cells. Immunohistochemistry staining revealed that the inner lining cells of glandular structures were positive for thyroid transcription factor-1 and surfactant protein-B, used as markers of alveolar epithelial cells, and were negative for p63. These findings for the first time demonstrated a rare alveolar epithelial differentiation of glandular inner lining cells in a mucoepidermoid carcinoma of the lung. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/7095988968057804